АНАЛІТИЧНИЙ РОЗРАХУНОК ВТРАТ ПОТУЖНОСТІ ВІД ВИХРОВИХ СТРУМІВ У РОТОРАХ З ПОСТІЙНИМИ МАГНІТАМИ - Макарчук , О.В. (Інститут електродинаміки НАН України, Київ, 2015)
An analytical solution of the Helmholtz equation for a conducting half-space in two-dimensional formulation is presented. The received spatial distribution of the magnetic vector potential is used for calculation of the current density and acquisition of dependencies, which allow to calculate the eddy current losses in the salient-pole rotor with exterior arrangement of permanent magnets. Two-dimensional FEM-model salient pole electrical machine with permanent magnet excitation was used to verify these results. The versions of calculating losses in the rotor for machines with halfclosed and open slots on the stator are compared. Reasonable accuracy of the offered analytical method is showed. The inexpediency of using open stator slots in high-speed machines with permanent magnets is confirmed, the recommendations about the choice of the type of stator windings are made. References 10, figures 5.